Pancasila Education in the Era of Technological Disruption: Challenges and Strategies for Strengthening Students' Nationality Character - Muhammad Fadli; Maswita (CV. Mitkom Indotama, 2026)
The era of technological disruption brought massive changes that not only transformed the industrial sector, but also the order of values, culture, and character of the nation. Students as a digital native generation are at the forefront of this change, but at the same time are the most vulnerable group to exposure to transnational ideologies, individualism, and digital polarization. This research aims to analyze the real challenges faced by Pancasila Education in higher education in the era of disruption, as well as formulate strategies to strengthen the adaptive national character for students. The research method used is literature review by collecting, reducing, and analyzing data from various scientific literature, books, and related reputable journals. The results of the study show that the main challenges of Pancasila Education include the obsolete conventional learning methodology and the massive flow of foreign information that obscures local values. The recommended strategies are the reconstruction of a digital-based curriculum, the use of media-rich learning, and the internalization of Pancasila values through an interactive cyber-pedagogical approach.